2008
DOI: 10.1177/0310057x0803600614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Magnesium Sulphate as an Adjuvant to Lignocaine for Intravenous Regional Anaesthesia for Upper Limb Surgery

Abstract: Several additives have been combined with local anaesthetics for intravenous regional anaesthesia to improve block quality, analgesia and to decrease tourniquet pain. Magnesium sulphate is one potential additive. This prospective, randomised, double-blinded study was conducted in 30 ASA physical status I or II patients undergoing upper limb surgery under tourniquet. In group L, patients received intravenous regional anaesthesia with lignocaine alone (9 ml of 2% lignocaine diluted with normal saline to total vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…Our results of recovery time of sensory blockade (mean ± SD) were found to be consistent with the finding of Narang et al 15 They found significant prolongation of recovery time of sensory block from 3.85 minutes in lignocaine alone and 5.71 minutes in lignocaine-magnesium group. Alayurt et al 17 found insignificant prolongation of recovery time of sensory block when clonidine was added to lignocaine for IVRA compared with lignocaine alone group but there was insignificant prolongation of recovery time of motor blockade (p > 0.05), which is consistent with our finding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results of recovery time of sensory blockade (mean ± SD) were found to be consistent with the finding of Narang et al 15 They found significant prolongation of recovery time of sensory block from 3.85 minutes in lignocaine alone and 5.71 minutes in lignocaine-magnesium group. Alayurt et al 17 found insignificant prolongation of recovery time of sensory block when clonidine was added to lignocaine for IVRA compared with lignocaine alone group but there was insignificant prolongation of recovery time of motor blockade (p > 0.05), which is consistent with our finding.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been found that magnesium when added to lignocaine improves the quality of anesthesia and analgesia in IVRA. 15 In the present study, we evaluated and compared the effects of adding either magnesium sulfate or clonidine to lignocaine in IVRA for upper limb surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulfate,6566 ketamine, and ketorolac66 have also been used as adjuvants in IVRA, with variable results 6667. Clonidine has also been successfully used 6870.…”
Section: Search Strategymentioning
confidence: 99%
“…A similar study concluded that there is increased incidence of transient pain on magnesium sulphate injection. 23…”
Section: Discussionmentioning
confidence: 99%